Catamenial haemoptysis: a rare cause. Issue 10 (October 1993) - Wood, D J; Krishnan, K; Stocks, P; Morgan, E; Ward, M J
Abstract : Since the first report of pulmonary endometriosis as a cause of catamenial haemoptysis all cases have been assumed to be due to pulmonary endometriosis, even in the absence of histopathological proof. A case is presented where the histological findings were of a pulmonary arteriovenous malformation.